PENGUATAN ECOLOGICAL CITIZENSHIP PESERTA DIDIK MELALUI PROGRAM BANK SAMPAH DI SMA NEGERI 9 BANDAR LAMPUNG - Mona Safitri; Muhammad Mona Adha; Nurhayati Nurhayati; Berchah Pitoewas; Rohman Rohman (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the strengthening of students’ ecological citizenship through the waste bank program at SMA Negeri 9 Bandar Lampung as a medium for ecological character education that fosters discipline, social responsibility, and environmental awareness. The research uses a qualitative approach with a case study method involving the principal, program supervisors, waste bank ambassadors, active students, and the Sahabat Gajah community. Data were collected through in-depth interviews, observation, and documentation and analyzed through data reduction, data display, and conclusion drawing. The results show that the strengthening of ecological citizenship occurs through active participation in waste bank program activities such as socialization, training, waste collection and sorting, ecobrick production, and waste management through a savings system in collaboration with Bank Mandiri. These activities habituate students to be disciplined, comply with procedures, and promote social responsibility and environmental awareness. The waste bank program provides a positive impact in shaping environmental care, responsibility, and cooperation, although there are challenges such as uneven participation and limited understanding of environmental preservation.